Postconflict Economics in Sub-Saharan Africa, Lessons from the Democratic Republic of the Congo - Clement, Jean. (Washington, D.C. : International Monetary Fund, 2005)
The Democratic Republic of the Congo is making significant strides on both the political and economic fronts to extricate itself from one of the bloodiest wars in African history. This remarkable turnaround offers other countries and the international community valuable lessons in preventing conflict and in coping with postconflict recovery. This book also provides a summary of the most recent research on conflict, an analysis of the causes of conflicts in Africa, and an outline of their key economic characteristics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet